Coordination Challenges in Collaborative Practices in the Prevention of Mother to Child Transmission of HIV in Tanzania - Shidende, Nima Herman; Grisot, Miria; Aanestad, Margunn (Journal of Health Informatics in Africa, 2014)
Background and Purpose: This paper describes some of the complexities that face health service provision in developing countries, with the motivation to inform design of appropriate information systems. In particular, we are interested in a better understanding of the challenges to coordination and collaboration between health staff that are located in different facilities and employed to work in different health programs. Methods: The study reported and analyzed in this paper was conducted in two districts in Tanzania. Using ethnographic data collection methods, we studied health workers’ practices of coordination and collaboration in Prevention of Mother to Child Transmission (PMTCT) services in Tanzania. Results: In our study we describe the collaboration required when managing patient trajectories of PMTCT patients across facilities and programs, and how contingencies may change the course of a patient trajectory. We provide a rich empirical description of coordination work in a resource constrained setting and we propose improvements to the design of both computer and paper-based information systems. Conclusions: The rich empirical description of coordination work in a resource constrained setting and our analysis of coordination challenges contribute to a better understanding that can strengthen collaboration and thus also improve health care provision. Keywords: Patient-Care Information Systems, Collaborative Practices, Coordination Mechanisms, Coordination Artefacts